Masterplan Kawasan Lubuak Tampuruang untuk Pengembangan Desa Wisata Guo - Ahmad Junaidi; Masril Syukur; Rudy Ferial; Zaini; Alfina Mursida Aljauhari; Tiara Assyifa Muthmainnah; Muhammad Ridho Hocksa; Nurhamidah Nurhamidah (Warta Pengabdian Andalas, 2024)
This community service activity was chosen to map the Guo Village area to identify existing potentials, such as tourism, regional development, and agriculture. The methods include photogrammetric mapping with drones and terrestrial measurements using Geodetic GPS. The data obtained was then processed using Civil 3D, Agisoft Metashape, and SketchUp software to produce topographic maps, detailed situations, and master plans. The results of this activity show that the mapping of the Guo River area succeeded in producing accurate and detailed maps, which can be used as the basis for regional development planning. In addition, this activity also allowed participants to improve their skills in using mapping technology integrated with Geographic Information Systems (GIS). Although this technology has developed, knowledge of its use in Indonesia is still minimal. Therefore, this activity is expected to encourage the wider use of mapping technology in Indonesia and accelerate the development of the Guo River region.